2009
DOI: 10.1002/atr.5670430205
|View full text |Cite
|
Sign up to set email alerts
|

A multiobjective model for maximizing fleet availability under the presence of flight and maintenance requirements

Abstract: Every aircraft, military or civilian, must be grounded for maintenance after it has completed a certain number of flight hours since its last maintenance check. In this paper, we address the problem of deciding which available aircraft should fly and for how long, and which grounded aircraft should perform maintenance operations, in a group of aircraft that comprise a combat unit. The objective is to achieve maximum availability of the unit over the planning horizon. We develop a multiobjective optimization mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The overall value intervals of the non-dominated schedules are now calculated with the sets of feasible weights according to equations (10) and (11). The intervals are depicted in Figures 7(a) and 7 Because there does not exist a unique preferred schedule on the basis of the dominance relations or the decision rules, the DM may wish to consider also the performance indicators listed in Section 3.1.…”
Section: Decision Support Phasementioning
confidence: 99%
“…The overall value intervals of the non-dominated schedules are now calculated with the sets of feasible weights according to equations (10) and (11). The intervals are depicted in Figures 7(a) and 7 Because there does not exist a unique preferred schedule on the basis of the dominance relations or the decision rules, the DM may wish to consider also the performance indicators listed in Section 3.1.…”
Section: Decision Support Phasementioning
confidence: 99%
“…The Military Flight and Maintenance Planning (MFMP) problem is a variant of the better known Civil Flight and Maintenance Planning (FMP) problem where all aircraft return to the base after each flight and fleet availability is prioritized over cost reduction. Initial work on the military variant was done by Sgaslik (1994) and since then different planning horizons have been studied: short term [e.g., Marlow and Dell (2017), Cho (2011), Vojvodić et al (2010)], medium term [e.g., Seif and Yu (2018), Verhoeff et al (2015), Kozanidis (2008), Hahn and Newman (2008), Pippin (1998)] and long term [e.g., Peschiera et al (2020)].…”
Section: State Of the Artmentioning
confidence: 99%
“…Each check requires a certain number of worker-hours and is scheduled every 200-400 flight hours. A Mixed-Integer Linear Programming (MILP) model was formulated in Kozanidis (2008) to solve simulated instances of 6-month horizons and a fleet of up to 30 aircraft. This model was applied in Gavranis and Kozanidis (2015) within an efficient solving method for a particular objective function case (maximizing overall sustainability), and Seif and Yu (2018) expanded this work to apply it for multiple check types and stations and a heterogeneous fleet.…”
Section: State Of the Artmentioning
confidence: 99%
“…Wei employed the game‐theoretical model to investigate how airport landing fees could influence airlines' decisions on aircraft size and service frequency. Kozanidis developed a multiobjective optimization model to maximize the availability of the aircraft. He showed that flight and maintenance requirements are two important factors for fleet planning while Givoni and Rietveld analyzed the environmental impacts of airlines' choice on aircraft size.…”
Section: Introductionmentioning
confidence: 99%